A Historical Myth? Matthew Flinders and the Quest for a Strait. Issue 1 (2nd January 2017) - Morgan, Kenneth
Abstract : This article takes issue with a recent argument, made by the late Rupert Gerritsen, that Matthew Flinders deliberately concocted a myth about a north–south strait dividing Australia in order to gain the attention and patronage of Sir Joseph Banks to support the first circumnavigation of Terra Australis in HMS Investigator in 1801–3. This article argues that Flinders did not create a myth but based his arguments on contemporary views that such a dividing strait might exist, backed up with cartographic evidence. Flinders' achievements in connection with the circumnavigation reflected the analytical mind that led him to search for a strait.